Testing the carotenoid-based sexual signalling mechanism by altering CYP2J19 gene expression and colour in a bird species. Issue 1938 (11th November 2020) - Cantarero, Alejandro; Andrade, Pedro; Carneiro, Miguel; Moreno-Borrallo, Adrián; Alonso-Alvarez, Carlos
Abstract : Ornaments can evolve to reveal individual quality when their production/maintenance costs make them reliable as 'signals' or if their expression level is intrinsically linked to condition by some unfalsifiable mechanism (indices). The latter has been mostly associated with traits constrained by body size. In red ketocarotenoid-based colorations, that link could, instead, be established with cell respiration at the inner mitochondrial membrane (IMM). The production mechanism could be independent of resource (yellow carotenoids) availability, thus discarding costs linked to allocation trade-offs. A gene coding for a ketolase enzyme (CYP2J19) responsible for converting dietary yellow carotenoids to red ketocarotenoids has recently been described. We treated male zebra finches with an antioxidant designed to penetrate the IMM (mitoTEMPO) and a thyroid hormone (triiodothyronine) with known hypermetabolic effects. Among hormone controls, MitoTEMPO downregulated CYP2J19 in the bill (a red ketocarotenoid-based ornament), supporting the mitochondrial involvement in ketolase function. Both treatments interacted when increasing hormone dosage, indicating that mitochondria and thyroid metabolisms could simultaneously regulate coloration. Moreover, CYP2J19 expression was positively correlated to redness but also to yellow carotenoid levels in the blood. However, treatment effects were not annulated when controlling for blood carotenoid variability, which suggests that costs linked to resource availability could be minor.